The incidence and characteristics of acute respiratory infection (ARI) after the earthquake in West Pasaman and Pasaman Districts, West Sumatra Province in 2022 - Isnaini; Fitry Yani Finny; Dianne Jurnalis Yusri; Mariko Rinang (E3S Web of Conferences)
In February 2022, an earthquake struck Pasaman City in West Sumatra and caused outbreaks of infectious diseases such as acute respiratory infections (ARI). Method: This study used an ecological design by collecting data on the population in West Pasaman and Pasaman Regency in 2022. 13 subjects in West Pasaman and 16 subjects in Pasaman were obtained. ARI cases were mostly found in the female (51.7%) and in the >5 years old group (55.2%). The nutritional status was mostly found in the undernourished category (79.3%). There was no significant relationship between the location of natural disasters and fever or cough in ARI patients (>0.05). Most subjects had a cold (75.9%). Most ARI patients from West Pasaman do not have families with smoking habits (84.6%), while most ARI patients from Pasaman have families with smoking habits (87.5%). There is a significant relationship between the location of natural disasters and families with smoking habits in ARI patients (<0.05). The prevalence of post-earthquake ARI in West Pasaman District and Pasaman Regency was higher among females, particularly in over 5 years old. The affected individuals had low nutritional status, with most of them had cold.